(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
The University of Dhaka has its own water supply system and entirely relies on groundwater. Ten groundwater samples were collected from 10 production wells of 120-320 m depth across the University campus from upper and lower Dupi Tila aquifers. The pH values revealed that water is mildly acidic to neutral and electrical conductivity (EC) values ranging from 325 to 654 μS/cm, indicating fresh groundwater. The total hardness (TH) of the samples ranges from 76-203 mg/L, suggesting moderately hard to very hard water. Of the ten groundwater samples, nine are of Ca-Mg-HCO3 type, whereas one shows Ca-Na-HCO3 type of groundwater. The saturation indices show that the groundwater samples are near-saturated for calcite, dolomite, gypsum, siderite, and rhodochrosite, indicating the low potential for dissolution-precipitation of these mineral. Notably, the results of WQI indicate that all the wells are safe for drinking. As of July 2023, the groundwater level was 72 m below ground level with a declination rate of 2.8 m/year. The estimated hydraulic conductivity values of 20 to 90 m/day and transmissivity values of 637 to 2740 m²/day suggest better permeability and water transmission potential within the lower aquifer. These results provide essential information for the university authority to implement appropriate strategies for efficient groundwater management. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(2), 2023, P 55-67